Unmodified Cre recombinase crosses the membrane - Will, Elke (Oxford University Press, 2002)
Site-specific recombination in genetically modified cells can be achieved by the activity of Cre recombinase from bacteriophage P1. Commonly an expression vector encoding Cre is introduced into cells; however, this can lead to undesired side-effects. Therefore, we tested whether cell-permeable Cre fusion proteins can be directly used for lox-specific recombination in a cell line tailored to shift from red to green fluorescence after loxP-specific recombination. Comparison of purified recombinant Cre proteins with and without a heterologous ‘protein transduction domain’ surprisingly showed that the unmodified Cre recombinase already possesses an intrinsic ability to cross the membrane border. Addition of purified recombinant Cre enyzme to primary bone marrow cells isolated from transgenic C/EBPα(fl/fl) mice also led to excision of the ‘floxed’ C/EBPα gene, thus demonstrating its potential for in vivo applications. We conclude that Cre enyzme itself or its intrinsic membrane-permeating moiety are attractive tools for direct manipulation of mammalian cells.